Transforming Growth Factor Beta 1 and Vascular Endothelial Growth Factor Levels in the Pathogenesis of Periodontal Disease. (May 2013) - Matarese, G.; Isola, G.; Anastasi, G.P.; Cutroneo, G.; Cordasco, G.; Favaloro, A.; Vita, G.; Vermiglio, G.; Milardi, D.; Zizzari, V.L.; Tetè, S.; Perillo, L.
Periodontal disease is characterized by inflammation and bone loss. The balance between inflammatory mediators and their counter-regulatory molecules may be fundamental for determining the outcome of immune pathology of periodontal disease. Cytokines play crucial roles in the maintenance of tissue homeostasis, a process which requires a delicate balance between anabolic and catabolic activities. In particular, two families of growth factors-such as transforming growth factor-β1 (TGF-β1) and vascular endothelial growth factor (VEGF) are thought to play important roles in modulating the proliferation and/or migration of structural cells involved in inflammation and regulation of immune responses. The aim of this work was to analyze gingival samples and periodontal tissue specimens collected from thirty-eight patients with chronic periodontal disease and from forty healthy individuals, in order to detect the expression and distribution of TGF-β1 and VEGF between the two groups. TGF-β1 and VEGF expression levels were detected using immunohistochemical analysis and computer-assisted morphometric analysis. The findings presented here suggest that biomarker such as TGF-β1 and VEGF have an important regulating role in the orchestration of the immune response, which in turn influence the outcome of disease establishment and evolution.